The Use of an Ambroxol Solution to Assess Acute Dermal Irritation on Rabbit Skin - Munifah Wahyuddin; Mukhriani; Vera Olfiana; Ika Puspita Sari; Rizka Humardewayanti Asdie; Titik Nuryastuti (Ad-Dawaa: Journal of Pharmaceutical Sciences, 2022)
Ambroxol can overcome infections due to the presence of biofilms in the body by interfering with the formation of sticky biofilms and reducing biofilm production, so it has the potential to be used in topical preparations for the treatment of infections. This study aimed to measure the irritating effect on the skin of rabbits resulting from the ambroxol solution to assess the safety of the ambroxol solution. The methods refers to BPOM 2020, namely by dabbing 0.5 ml of ambroxol solution on the back skin of rabbits, then covering it with gauze and non-irritant plasters, after 4 hours of cleaning of residues is then observed at 1 , 24, 48 and 72 hours to see whether or not there was an effect of erythema and edema arising from the influence of the experiment, and at the end of the investigation, a histopathological test was carried out. The results of the research are Macroscopically the ambroxol solution did not show any erythema and edema, so the primary irritation index score was obtained for all test solutions with a score of 0. In contrast, in the microscopic irritation test, the score for erythema was 4 and for edema was 3. . From this research, it can be concluded that the ambroxol solution non-irritating to the skin. KEYWORDS: Biofilm, ambroxol solutions, acute irritation test.